Production and properties of Xylanase from thermophilic Bacillus sp. - Cordeiro,Carlos Alberto Martins (2002)
An aerobic, thermophilic, xylanolytic bacterium was isolated from local soil. The results of 16S rRNA sequence comparisons indicated that the isolate was closely related to Bacillus caldoxylolyticus and Bacillus sp strain AK1. These organisms exhibited 94% levels of ribossomal DNA sequence homology. Studies on the xylanase characterisation from liquid cultures grown on beechwood xylan revealed that the enzyme retained 100% of activity for 2 hours at temperatures ranging from 30 to 50º C, while at 60, 70 and 100º C, 10%, 11% and 29% of the original activities were lost, respectively. The optimum pH of the enzyme was found to be between 6.5 and 7.0. After incubation of crude enzyme solution for 24 hours at 25º C and at pH 5.5 to 8.0, a decrease of about 12% of its original activity was observed.